AN ANALYSIS OF THE GROUNDING SYSTEM IN THE 20 KV TRANSFORMER USING ROD ELECTRODES IN PT. PLN (PERSERO) ULP PARAPAT - Fahri Lubis; Hamdani Hamdani (Sean Institute, 2023)
The grounding/earthing system aims to secure electrical equipment and maintain the safety of humans who are at the place where the disturbance occurs by channeling the fault current to the ground/earth. Therefore, the grounding system is very important in the continuity of electric power distribution. Good grounding implementation obtains a resistance value according to the PUIL standard with a value of < 5 Ω. The value of grounding resistance is strongly influenced by the number of electrodes, the depth of the implanted electrodes, the distance between the electrodes, the size of the electrodes and the state of the ground where the electrodes are installed. In a certain area, it is often found that several types of soil have different soil resistivity values.